Re-Evaluating Contractual Relativity: Third-Party Effects in Islamic and Positive Legal Frameworks - Chami, Yassine; Khater, Maya (Mazahib, 2025)
This study compares the principle of contractual relativity and its exceptions regarding third-party effects in Islamic jurisprudence and positive law. Employing a doctrinal-comparative methodology, it identifies key convergences and divergences in how both systems treat general successors, special successors, and creditors. The research finds that while both systems uphold the core principle, they develop distinct mechanisms for third-party protection, rooted in different foundational philosophies (Sharia vs. autonomy of will). A key novelty lies in the critical analysis revealing that classical juristic tools (like waqf, wasiyya) serve functions analogous to, but conceptually distinct from, positive law exceptions (like stipulation pour autrui). The study concludes that technological advancements necessitate contextual application of the principle, not its abandonment, and offers targeted recommendations for legal harmonization and judicial training to enhance transactional justice and stability.